2009
DOI: 10.3171/2009.4.focus0965
|View full text |Cite
|
Sign up to set email alerts
|

Complications of decompressive craniectomy for traumatic brain injury

Abstract: Decompressive craniectomy is widely used to treat intracranial hypertension following traumatic brain injury (TBI). Two randomized trials are currently underway to further evaluate the effectiveness of decompressive craniectomy for TBI. Complications of this procedure have major ramifications on the risk-benefit balance in decision-making during evaluation of potential surgical candidates. To further evaluate the complications of decompressive craniectomy, a review of the literature was performed follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
302
1
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(336 citation statements)
references
References 99 publications
5
302
1
10
Order By: Relevance
“…The conversion of the cranium from a ''closed box'' to an ''open box'' alters the barometric pressure, cerebrospinal fluid (CSF) flow and the cerebral blood flow (CBF). However, this alteration carries benefits as well as risks [1]. Numerous complications may arise as a result of the pathophysiological events that accompany removal of a large piece of skull bone, and these complications arise in a sequential fashion at specific time points following the surgical decompression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of the cranium from a ''closed box'' to an ''open box'' alters the barometric pressure, cerebrospinal fluid (CSF) flow and the cerebral blood flow (CBF). However, this alteration carries benefits as well as risks [1]. Numerous complications may arise as a result of the pathophysiological events that accompany removal of a large piece of skull bone, and these complications arise in a sequential fashion at specific time points following the surgical decompression.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, there develop new cognitive, sensorimotor, neurological and psychological deficits which are incorporated in the syndrome complex called the sinking skin flap syndrome (SSFS), also called the syndrome of the trephined (ST), or the motor trephine syndrome (MTS). In the longer term, a persistent vegetative state is the most devastating of outcomes of decompressive craniectomy [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, spontaneous intracranial epidural hematoma has been infrequently reported in association with cranial decompression, 10) coagulopathy, 13) sphenoid sinusitis, 12) ruptured middle meningeal artery psudoaneurysm, 4) or cranial metastasis. 6) However, spontaneous intracranial epidural hematoma as a complication of spine surgery is extremely unusual, with only one such case described in an adolescent, 11) who underwent resection of a thoracic spine lesion and developed acute supratentorial epidural hematoma postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…81 In a study in cats Shapiro et al showed that when a portion of the skull is removed, the compliance (pressure volume index) of the brain increases and the CSF outflow resistance decreases; 78,79 therefore, according to the Davson formula above, 23 since CSF outflow resistance approaches 0, again ICP becomes dependent on cerebral venous pressure. 67 Moreover, dural open-ing after craniectomy further increases brain compliance and decreases CSF outflow resistance.…”
Section: Ventriculomegaly Associated With Craniectomymentioning
confidence: 99%
“…31 A well-known complication after craniectomy is ventriculomegaly. 81 In 2007 Waziri et al reported an 88% incidence of communicating hydrocephalus in their cohort of 17 patents who had undergone hemicraniectomy, half of whom required ventriculoperitoneal shunts. 90 The study excluded patients who had undergone hemicraniectomy for subarachnoid hemorrhage, intraventricular hemorrhage, or infection, that is, confounding variables that may have contributed independently to hydrocephalus.…”
Section: Ventriculomegaly Associated With Craniectomymentioning
confidence: 99%